POLA PENGGUNAAN SITUS JEJARING SOSIAL SEBAGAI MEDIA PEMBELAJARAN UNTUK MAHASISWA - Almed Hamzah (Teknoin, 2015)
Social networking sites are very popular. At this time a lot of social networking sites that emerge and evolve. Some of which the most popular are Facebook, Twitter, path, myspace. These sites are popular because it has many users from various groups including the student. Students including active users of social networking sites. The majority of the students even already have an account at more than one site of several social networking sites. Social networking sites can be used by students for a variety of purposes, one of them as a medium of learning. This research is a case study to explore the use of social networking sites as a medium of learning among the students. A total of 42 students were respondents in this study. Results of the analysis found that social networking sites are already quite familiar among students as a means to socialize as well as a learning medium. In addition, it features a social networking site which is used as a medium of learning is not much different from the usual features that are used for other purposes.